Redesign of Rice Planting Tools Using an Ergonomics Approach - Andriani, Meri; Irwanda, Muhammad Fanny; Nadya, Yusri (Politeknik Negeri Lhokseumawe, 2024)
Farmers' work in planting rice is always with a bent posture, causing complaints of musculoskeletal disorders, this is a problem in research. The aim of the research is to identify farmers' complaints of musculoskeletal disorders when planting rice and determine the size of ergonomic tools. The method used is standard Nordic questionnaires to determine the point of complaint among farmers, anthropometry and percentiles are used to design the tool. Statistical tests are used to see valid, uniform, and normal data. Results and discussion, in the standard Nordiq questionnaire, it was found that farmers experienced more than 50% complaints of severe pain in the waist, left calf, right calf, left ankle, right ankle, left foot, and right foot. The design uses eight anthropometric dimensions: standing elbow height, palm length, palm width, middle finger length, shoulder width, body thickness, upper arm length, and hand length. All anthropometric dimensions were declared uniform, in the data adequacy test they were declared valid, and in the normality test, all data were declared normally distributed. The 5th percentile is used for the dimensions of shoulder width, standing elbow height, and palm length, and the 95th percentile is used for the dimensions of palm width, middle finger length, body thickness, upper arm length, and hand length.In conclusion, complaints of musculoskeletal disorders were identified as very painful, located at the point of complaint of the waist. The rice planting tool has ergonomic dimensions, the height of the tool is 88.1 cm, the diameter of the tool handle is 8.13 cm, the length of the handle is 11.4 cm, and the distance between the handle and the brake is 9.32 cm. The dimensions of the rice seed bag are 33.70 cm wide, the distance between the front and back of the bag is 23.19 cm, the bag height is 35.64 cm, and the bag length is 20.5 cm.